Contribution of processing parameters on void content in the vacuum bagging configurations of L-shaped composite laminates - Hassan, M.H. (Springer London, 2017)
Out-of-autoclave (OoA) curing is a potential solution in achieving good part quality of low void content at economical manufacturing process compared to the autoclave counterpart. However, with the absence of high pressure in the OoA process, removing voids and volatiles depends only on the vacuuming through the bagging system. It was previously highlighted that different bagging configurations may affect the quality of the cured composites, with the issues remained at the curved section of complex laminates, mostly originated from the bagging arrangement itself. This work presents an experimental analysis on the various bagging configurations in a vacuum bagging process of L-shaped composite. Statistical contributions of the polytetrafluoroethylene (PTFE), edge breather and intensifier in eight different bagging configurations on void content of the complex-shaped laminates were quantified. The correlation between the resin mass loss and void formation at the corner regions was also analysed. The results indicated that the PTFE configuration produced higher void content at 9.66. However, when the VBO and intensifier were included in the bagging setup, the void content achieved minimum values of 4.92 and 4.94, respectively. Additionally, when both parameters were combined, the bagging configuration further reduced the void content to 3.85 at the curved section of the L-shaped laminate. © 2017, Springer-Verlag London.